Solid and hazardous waste management : - Rao, M. Narayana (Butterworth-Heinemann, 2017)
Solid and Hazardous Waste Management: Science and Engineering presents the latest on the rapid increase in volume and types of solid and hazardous wastes that have resulted from economic growth, urbanization, and industrialization and how they have challenged national and local governments to ensure effective and sustainable management of these waste products. The book offers universal coverage of the technologies used for the management and disposal of waste products, such as plastic waste, bio-medical wastes, hazardous wastes, and e-wastes.